Conscientious objectors in Israel : citizenship, sacrifice, trials of fealty - Weiss, Erica, 1981- (Ethnography of political violence., 2014)
Conscientious Objectors in Israel chronicles the personal experiences of two generations of Jewish Israeli conscientious objectors as they grapple with their consciences under the pressure of justifying their actions to the Israeli state and society.